Time Course of Altered Sensitivity to Inhibitory and Excitatory Agonist Responses in the Longitudinal Muscle–Myenteric Plexus and Analgesia in the Guinea Pig after Chronic Morphine Treatment - Barrett, Dane M.; Maguma, Hercules T.; Taylor, David A. (Frontiers in Pharmacology, 2012)
Tolerance that develops after chronic morphine exposure has been proposed to be an adaptive response that develops and decays over a defined time course. The present study examined the development of tolerance to the acute hypothermic and analgesic effects of morphine and correlated the time course for the desensitization in vivo with the reduced responsiveness to DAMGO and 2-CADO and increased responsiveness to nicotine of the longitudinal muscle/myenteric plexus (LM/MP) preparation in vitro. Assessment was performed at various times after morphine or placebo pellet implantation. Morphine produced a modest hypothermic response to which no tolerance developed. However, the development of tolerance to the analgesic effect of morphine, the inhibitory effect of DAMGO and CADO on neurogenic twitches of the LM/MP and hypersensitivity to the contractile response to nicotine was observed to occur in a time-dependent manner. The alterations in sensitivity to DAMGO, nicotine and responsiveness to morphine analgesia occurred between days 4 and 10 and returned to normal by day 14 post-implantation. In contrast, sensitivity of LM/MP preparations to 2-CADO displayed a similar time-dependent onset but the tolerance persisted beyond 14 days after implantation. These data suggest that the heterologous tolerance that develops after chronic morphine treatment is time-dependent and persistent but, ultimately returns to normal in the absence of any intervention. Furthermore, the data suggest that the basis of the adaptive phenomenon may involve multiple cellular mechanisms including the modulation of cell excitability and normal physiology but the consequences of the adaptation extend to all effects of the agonist.